Attracting New Maine Residents: The Effects of Educational Attainment and Age on Interstate Mobility - Leparulo, Paul (Maine Policy Review, 2019)
Maine faces population issues that pose considerable headwinds to the state’s economic growth and prosperity. Restoring a more robust growth path will require attracting new residents to the state. This article examines some of the factors that cause individuals to relocate across state lines. I quantify the relationship between educational attainment, age, and interstate mobility and find that having a bachelor’s degree or higher has a large, positive, statistically significant effect on the probability of making an interstate move. The effect is strongest for people in their twenties (the youngest age in the restricted sample) and diminishes with age. The results indicate that age has a larger diminishing effect on those with higher educational attainment. I also find that homeownership substantially lowers the probability of a move. Limited data indicates similar results would hold for movers to Maine. The findings suggest that the development of a state’s job market is a critical dimension in attracting and retaining residents.
Keywords: demographics; interstate moves; bachelor's degree; age; homeownership